TRPA1-dependent calcium transients and CGRP release in DRG neurons require extracellular calcium - Gebhardt, Lisa; Kichko, Tetyana; Fischer, Michael J.M.; Reeh, Peter (The Journal of Cell Biology, 2020)
Shang et al. (2016. J. Cell Biol.https://doi.org/10.1083/jcb.201603081) reported that activation of lysosomal TRPA1 channels led to intracellular calcium transients and CGRP release from DRG neurons. We argue that both findings are more likely due to influx of insufficiently buffered extracellular calcium rather than lysosomal release.
CRIS-Team Scopus Importer:2020-06-02